Defective interferon gamma production by tumor-specific cd8+ T cells is associated with 5′methylcytosine-guanine hypermethylation of interferon gamma promoter - Abd Hamid, M; Yao, X; Waugh, C; Rosendo-Machado, S; Li, C; Rostron, T; Frankland, J; Peng, Y; Dong, T (Frontiers Media, 2020)
Interferon gamma (IFNγ) supports effector responses of CD8+ cytotoxic T lymphocytes (CTLs) and is a surrogate marker for detection of antigen-specific T cells. Here, we show that tumor-specific CTL clones have impaired IFNγ expression and production upon activation. Assessment of the relationship between IFNγ production and the 5′methylcytosine-guanine (CpG) dinucleotide methylation of the IFNγ promoter using bisulfite treatment has shown that IFNγ− CTL clones accumulates CpG hypermethylation within the promoter at key transcription factor binding sites (−186 and −54), known to be vital for transcription. We confirmed these findings using ex vivo isolated and short-term expanded bulk tumor-specific CTL lines from four cancer patients and demonstrated that IFNγ methylation inversely correlates with transcription, protein level, and cytotoxicity. Altogether, we propose that a sizeable portion of human tumor-specific CTLs are deficient in IFNγ response, contributed by CpG hypermethylation of the IFNγ promoter. Our findings have important implications for immunotherapy strategies and for methods to detect human antigen-specific T cells.